Design and validation of an instrument to determine the pharmacotherapeutic profile of pediatric and adult inpatients in pharmaceutical care consultation at IPS Colsubsidio, Bogotá D.C., 2025 (Universitas Scientiarum, 2025)
In clinical pharmacy, the Pharmacotherapeutic Profile (PP) serves as a key tool for documenting patient information, treatment, and clinical progression. At IPS Colsubsidio, PP is used for pharmacotherapeutic follow-up; however, it presents limitations: a design focused on dispensing that does not adapt to clinical documentation needs, the absence of a coded format hindering information analysis and organization, and institutional perception of the pharmacist as an administrative rather than a clinical professional. The objective was to design and conduct face and content validation of an instrument to determine the PP of hospitalized pediatric and adult patients at IPS Colsubsidio between February and May 2025. The development and validation studies were conducted in five phases: (1) construct definition; (2) literature review; (3) item identification, domain specification, and preliminary instrument design; (4) face and content validation through the Delphi technique, conducted in two rounds with expert reviewers using Face and Content Validity Ratio (FVR, CVR) and Face and Content Validity Index (FVI, CVI), both evaluated through a Likert scale; (5) final PP design. A total of 75 items were collected from 24 reviewed references and subsequently validated through face and content validity by six pharmacists. After implementing suggested adjustments, a final PP was designed, comprising 72 items distributed across six domains, with high FVI and CVI values of 0.96. The PP optimizes clinical and pharmacotherapeutic data collection and analysis, enabling personalized care and enhancing the pharmaceutical care program.